2005
DOI: 10.1086/431151
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Serotype 1Streptococcus pneumoniaeMeningitis in Northern Ghana with Features That Are Characteristic ofNeisseria meningitidisMeningitis Epidemics

Abstract: The S. pneumoniae ST217 clonal complex represents a hypervirulent lineage with a high propensity to cause meningitis, and our results suggest that this lineage might have the potential to cause an epidemic. Serotype 1 is not included in the currently licensed pediatric heptavalent pneumococcal vaccine. Mass vaccination with a less complex conjugate vaccine that targets hypervirulent serotypes should, therefore, be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
159
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(177 citation statements)
references
References 32 publications
15
159
2
1
Order By: Relevance
“…Although the majority of isolates encountered in this investigation were recovered from the south-eastern region, in particular from São (Spratt & Greenwood, 2000). Examples of clonal expansion associated with serotype 1 isolates have been described recently: the epidemic pneumococcal meningitis that occurred in the Africa meningitis belt, specifically in northern Ghana and Burkina Faso, were caused by serotype 1 isolates of the hypervirulent ST217 clonal complex (Leimkugel et al, 2005;Yaro et al, 2006), and the emergence of a single serotype 1 lineage (ST306) was reported among healthy carriers attending day-care centres in Portugal after the introduction of a seven-valent conjugate vaccine (Nunes et al, 2008).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Although the majority of isolates encountered in this investigation were recovered from the south-eastern region, in particular from São (Spratt & Greenwood, 2000). Examples of clonal expansion associated with serotype 1 isolates have been described recently: the epidemic pneumococcal meningitis that occurred in the Africa meningitis belt, specifically in northern Ghana and Burkina Faso, were caused by serotype 1 isolates of the hypervirulent ST217 clonal complex (Leimkugel et al, 2005;Yaro et al, 2006), and the emergence of a single serotype 1 lineage (ST306) was reported among healthy carriers attending day-care centres in Portugal after the introduction of a seven-valent conjugate vaccine (Nunes et al, 2008).…”
Section: Resultsmentioning
confidence: 83%
“…Serotype 1 has specific epidemiological features, including: (i) a low colonization frequency, even in populations in which serotype 1 is a frequent cause of pneumococcal infections (Laval et al, 2006;Normark et al, 2001;Nunes et al, 2008); (ii) the ability to cause outbreaks in communities and in crowded and closed institutions (Dagan et al, 2000;Leimkugel et al, 2005); (iii) an association with severe episodes of pneumonia and empyema in children (Byington et al, 2006); and (iv) susceptibility to most antimicrobial agents (Klugman & Koornhof, 1988). Recently, some authors have speculated that isolates of serotype 1, which are known to have a highly invasive potential, behave as primary pathogens, whereas other capsular types demonstrate opportunistic features (Garau & Calbo, 2007;Hausdorff, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A region of sub-Saharan Africa extending from Ethiopia to Senegal, designated "the African meningitis belt", has been particularly vulnerable to meningococcal disease epidemics [4]. In addition to sporadic disease which occurs mainly during the annual dry season, meningitis epidemics have occurred in the African meningitis belt every 8 -12 years over the past 100 years [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to sporadic disease which occurs mainly during the annual dry season, meningitis epidemics have occurred in the African meningitis belt every 8 -12 years over the past 100 years [4]. Ghana along with other countries in West and East Africa lies within the African meningitis belt (as shown in Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation